Fire Protection of Utility Pine Wood Poles - José Saporiti Machado; Elisabete Cordeiro; Sofia Knapic; Telmo Morgado; Alfredo M. P. G. Dias (Fire)
The increasing frequency and intensity of wildfires are affecting the use of wood products in rural areas as well as at the wildland–urban interface. The enhancement in wood products’ reaction/resistance to fire is a concern often raised by national authorities. In the present study, different fire protection measures were applied to utility wood poles aiming to protect them from wildfires, ensuring their reuse in safe conditions while preventing them from contributing to the propagation of forest fires, particularly surface fires. Two of the solutions tested were based on intumescent paints, while the other one involved a system that completely covers the poles’ exteriors (a fabric-protection layer mechanically applied to the surface of the pole). These solutions were initially assessed in small-scale laboratory tests. Following these initial tests, a selected solution based on fabric protection was tested under simulated wildland fire conditions. The results obtained showed that fabric-based protection delivered satisfactory results, being easily applied on site, allowing the protection of poles already in service and the replacement of fire protection devices after a fire occurs.